2021
DOI: 10.1002/ange.202014677
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photoinduced Electron Transfer in POM‐Bodipy Hybrids by Controlling the Environment: Experiment and Theory

Abstract: The optical and electrochemical properties of a series of polyoxometalate (POM) oxoclusters decorated with two bodipy (boron‐dipyrromethene) light‐harvesting units were examined. Evaluated here in this polyanionic donor‐acceptor system is the effect of the solvent and associated counterions on the intramolecular photoinduced electron transfer. The results show that both solvents and counterions have a major impact upon the energy of the charge‐transfer state by modifying the solvation shell around the POMs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Atomistic MD simulations with explicit solvent molecules were performed to determine the behaviour of PcLn-{V12} and (PcLn)2-{V12} (for Ln = Lu) in pure CH2Cl2 using the GROMACS 5.1.2 code 54,55 and a modified AMBER 99 Force Field, 56 which has been successfully employed in previous studies of the dynamic behaviour of POMs in different environments, including aggregation phenomena. [57][58][59] The MD trajectories were calculated imposing 3D periodic boundary conditions. Two different fundamental cubic boxes were used: a (8.5 nm) 3 box containing 8 units (PcLn-{V12} or (PcLn)2-{V12} anions) for the 20 mM (high concentration) solution, and a (11.6 nm) 3 box containing 5 units for the 5 mM (low concentration) solution.…”
Section: Studymentioning
confidence: 99%
“…Atomistic MD simulations with explicit solvent molecules were performed to determine the behaviour of PcLn-{V12} and (PcLn)2-{V12} (for Ln = Lu) in pure CH2Cl2 using the GROMACS 5.1.2 code 54,55 and a modified AMBER 99 Force Field, 56 which has been successfully employed in previous studies of the dynamic behaviour of POMs in different environments, including aggregation phenomena. [57][58][59] The MD trajectories were calculated imposing 3D periodic boundary conditions. Two different fundamental cubic boxes were used: a (8.5 nm) 3 box containing 8 units (PcLn-{V12} or (PcLn)2-{V12} anions) for the 20 mM (high concentration) solution, and a (11.6 nm) 3 box containing 5 units for the 5 mM (low concentration) solution.…”
Section: Studymentioning
confidence: 99%
“…33 MeCN. 23 The organotin derivatives display higher negative charge compared to the organosilyl derivatives,…”
Section: K Momentioning
confidence: 99%
“…21,22 Precious metal-free photosensitizers such as zinc porphyrin, perylene, pyrene and boron dipyrromethene (bodipy) have also been applied. 13,14,17,23,24 In these systems, charge-transfer from the sensitizer to the POM occurs either through space or through the bridge, depending on the structure. 25 In bodipy photosensitized POM conjugates, we previously showed that the occurrence and kinetics of photoinduced electron transfer was strongly dependant on the redox properties of both POM and the bodipy sensitizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the πdelocalization that is symmetrically extended twice or even more, reducing both internal and external reorganization energy. [17][18][19][20][21] Therefore, despite the perhaps intense emission, the small Stokes shift causes significant reabsorption and hence radiative quenching of the emission. In sharp contrast, the asymmetric structure results in uneven π-delocalization, increasing the internal reorganization energy and hence the Stokes shift for reducing the reabsorption.…”
Section: Introductionmentioning
confidence: 99%